Lonergan and Kant - Sala, Giovanni B. (Book collections on Project MUSE., 1994)
The final paper discusses Kant's resolution of the question regarding the agreement of a priori concepts with things, and finds in Lonergan's work an alternative position on correspondence and truth. Each essay is a model of careful and thorough scholarship, and also - surprising in a book of such proportions - of clarity. Lonergan appeals several times in Insight to the device of 'Clarification by Contrast.' Sala's essays show us in intricate detail how illuminating such comparisons can be.